2017
DOI: 10.1111/sum.12390
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting physical and biochemical properties of orchard soils suppressive and conducive to Fusarium wilt of banana

Abstract: Fusarium wilt disease is one of the most serious soil-borne diseases in banana orchards worldwide. Some soils are suppressive to Fusarium wilt, although the mechanisms are still unclear. In this study, two typical banana-growing soils (ultisol and inceptisol), which were either suppressive or conducive to Fusarium wilt, were collected from Hainan, China. Particle size distribution, pH values, electrical conductivity (EC), enzyme activities and microbial polymerase chain reaction amplification of the soil sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…It is mediated by soil organic carbon (SOC), biota, ionic bridging, clay and carbonates [45]. Li et al [46] analyzed two typical banana-growing soils (ultisol and inceptisol), which were either suppressive or conducive to the FW of banana from Hainan, China. They found that the suppressive soils had significantly more >2 and <0.053 mm aggregates, had a comparatively even size distribution of aggregates within the range of 0-0.25 mm, and a higher total carbon, total nitrogen and soil enzyme activity in the aggregates.…”
Section: Land and Soil Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mediated by soil organic carbon (SOC), biota, ionic bridging, clay and carbonates [45]. Li et al [46] analyzed two typical banana-growing soils (ultisol and inceptisol), which were either suppressive or conducive to the FW of banana from Hainan, China. They found that the suppressive soils had significantly more >2 and <0.053 mm aggregates, had a comparatively even size distribution of aggregates within the range of 0-0.25 mm, and a higher total carbon, total nitrogen and soil enzyme activity in the aggregates.…”
Section: Land and Soil Physical Propertiesmentioning
confidence: 99%
“…Concerning pH, Foc can grow in vitro in a wide pH range (optimal, 7.5-8.5) [36,46]. Under field conditions, some works have reported that, in the banana zones of Central America, the fungus seems to have different ranges of optimal pH depending on the soil type.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…8). Li et al (2018) suggesting that EC could be a new tool for monitoring soil-borne disease. Arif et al (2021) found that the relative electrical conductivity of roots inoculated with P. brassicae was 2.85 times greater than that of the control, which may be due to the increased membrane permeability and cell membrane damage.…”
Section: Ec Was Positively Correlated With DI Of Clubroot Disease and The Correlation Was The Highest Among All Soil Propertiesmentioning
confidence: 99%
“…PS particles at 50 μm cannot readily be accumulated by tomatoes, and as such, the mechanism of enhanced bacterial wilt from this material will be different from that of smaller plastics. As noted above, the occurrence of plant disease is regulated by soil physicochemical properties, the soil microbial community, and the innate response of a plant to pathogen presence and damage. ,, Thus, 30 nm-PS and 50 μm-PS were selected as representative plastics that can and cannot be accumulated, respectively, by tomato to further investigate the mechanisms by which these contaminants promote the disease severity of bacterial wilt. The exposure to 30 nm-PS significantly decreased the yield of tomato in healthy and infected treatments by 17.4 and 24.9%, respectively, while 50 μm-PS had no significant effects (Figure S8A).…”
Section: Resultsmentioning
confidence: 99%